ANALYSIS OF POTENTIALS BANGUN-BANGUN (Coleus amboinicus) AND BELIMBING WULUH (Averhoa bilimbi) PLANTS, AS ANTIMICROBIAL MATERIAL - Riyanto; Nasution, jamilah; Saragih, Winda; Saragih, Weni (Biospecies, 2020)
This study aims to analyze what anti-microbial power contained in plants and starfruit plants, and compare which plants are stronger anti-microbial power. The method used in this study is an experimental method, with Escherichia coli bacteria as a representative of disease-causing bacteria. The data obtained were analyzed using the ANOVA test. Based on the results of the study, the stems and leaves of the plant leaves and leaves of star fruit positive containing the composition of secondary metabolites saponins that have antimicrobial power that utilizes the growth ability of E coli. The average diameter of inhibitory zones of plant extracts of wake-up and starfruit â‰¥ 21 mm, so it is categorized as having strong antimicrobial power. However, the inhibitory zones formed have not been able to match or beat the inhibition zones C 25% (52.54 and 43.1), ciprofloxacin (64.41), which is antibiotics sold on the market that are made with positive control.